International Alzheimer's Disease Research Portfolio (IADRP) aims to capture global Alzheimer's disease research funding. Issue 3 (1st May 2014) - Liggins, Charlene; Snyder, Heather M.; Silverberg, Nina; Petanceska, Suzana; Refolo, Lorenzo M.; Ryan, Laurie; Carrillo, Maria C.
Abstract: Alzheimer's disease (AD) is a recognized international public health crisis. There is an urgent need for public and private funding agencies around the world to coordinate funding strategies and leverage existing resources to enhance and expand support of AD research. To capture and compare their existing investments in AD research and research‐related resources, major funding organizations are starting to utilize the Common Alzheimer's Disease Research Ontology (CADRO) to categorize their funding information. This information is captured in the International Alzheimer's Disease Research Portfolio (IADRP) for further analysis. As of January, 2014, over fifteen organizations from the US, Canada, Europe and Australia have contributed their information. The goal of the IADRP project is to enable funding organizations to assess the changing landscape of AD research and coordinate strategies, leverage resources, and avoid duplication of effort.